KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS CERPEN TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMK NEGERI 9 PADANG - Assadiyah, Herfina; Thahar, Harris Effendi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study was categorized into three. First, to describe the reading skills in understanding the short story of the second-year students at SMK Negeri 9 Padang. Second, to describe the writing skills of a short story for the second year students at SMK Negeri 9 Padang. Third, to describe the contribution of reading short story comprehension into the writing skills of a short story made by the second year students of SMK Negeri 9 Padang. The design of this research was quantitative with a descriptive method. Then, this study also was a correlational design. The population of this study was the second - grade students at SMK Negeri 9 Padang in the academic year 2018/2019 for about 232 students. The sample of this study was taken by using a proportional random sampling technique (20%), which was 46 students. The data of this study were the results of reading skills tests for understanding short story texts and the results of the text writing short story texts. The instrument of this study was an objective test to measure reading skills in understanding short story texts and performance tests to measure short story texts writing skills. There were several results of this study. First, the writing skill of the short story text of the second-year students at SMK Negeri  Padang was more than adequate (LdC). Second, reading skills understanding the short text of the second-year students at SMK Negeri 9 Padang was in a Good qualification (B). Third, reading skills understanding the short story of the second-year students at SMK Negeri 9 Padang contributed 72.1% to the short story writing skills of the second year students of SMK Negeri 9 Padang.         Kata Kunci: Kontribusi, Keterampilan Membaca Pemahaman Teks Cerpen, Keterampilan Menulis Teks Cerpen